Microencapsulated essential oils alleviate diarrhea in weaned piglets by modulating the intestinal microbial barrier as well as not inducing antibiotic resistance: a field research - Xu, Xianbin; Mo, Kaibin; Cui, Can; Lan, Yanhua; Ling, Lifang; Xu, Jinxia; Li, Li; Huang, Xianhui (Frontiers in Veterinary Science, 2024)
Microencapsulated essential oils (MEO)have been used as antibiotic alternatives that can be applied to alleviate diarrhea in weaning piglet. We examined a large group of weaned piglets and incorporated essential oil containing thymol (2%), carvacrol (5%) and cinnamaldehyde (3%) in the feed of weaned piglets on an intensive production farm. The piglets were divided into four groups; Control (no additions) and chlortetracycline (Chl), essential oil (EO) and microencapsulated essential oil (MEO) were fed ad libitum over a 28-day trial period. We found MEO significantly reduced the incidence of diarrhea in the piglets that was also accompanied by increased average daily weight gains from days 14-28 (P<0.05). MEO enhanced the antioxidant capacity in the piglets and serum total antioxidant capacity (T-AOC) and glutathione peroxidase (GSH-px) levels were significantly increased (P<0.05). MEO also significantly reduced expression of genes related to ileal inflammation (IL-6, TNF-α and TGF-β1) (P<0.05) and significantly (P<0.05) increased in sIgA antibody levels. MEO influenced the composition of the intestinal microbiome and reduced Bacteroidota (P<0.05) and thus altered the Firmicutes/Bacteroidota ratio. However, none of the treatments produced significant changes in the most common tetracycline resistance genes (P >0.05). Metagenomic analysis indicated that MEO impacted DNA expression, virulence factors, antioxidant activity and antimicrobial activity. Metabolomic analysis of the intestinal content also indicated that MEO impacted tyrosine metabolism and primary bile acid biosynthesis suggesting improved intestinal health and nutrient absorption. This study paves the way for further research into the development and optimization of MEO-based interventions aimed at improving piglet health and performance while also providing a reference for reducing reliance on antibiotics in animal agriculture.